A Comparison of Two Excreta Collection Tecnique (Tray vs Plastic Bag) for Amino Acids Digestibility and Metabolizable Energy Determinatons of Rapeseed Meals in Adults Cockerels - Zuprizal (Zuprizal); M. Larbier (Faculty of Animal Science, Universitas Gadjah Mada, 1993)
Artikel dalam bentuk PDF